Ultrasound‐Enhanced siRNA Delivery Using Magnetic Nanoparticle‐Loaded Chitosan‐Deoxycholic Acid Nanodroplets. Issue 8 (13th February 2017) - Lee, Jeong Yu; Crake, Calum; Teo, Boon; Carugo, Dario; de Saint Victor, Marie; Seth, Anjali; Stride, Eleanor
Abstract : Small interfering RNA (siRNA) has significant therapeutic potential but its clinical translation has been severely inhibited by a lack of effective delivery strategies. Previous work has demonstrated that perfluorocarbon nanodroplets loaded with magnetic nanoparticles can facilitate the intracellular delivery of a conventional chemotherapeutic drug. The aim of this study is to determine whether a similar agent can provide a means of delivering siRNA, enabling efficient transfection without degradation of the molecule. Chitosan‐deoxycholic acid nanoparticles containing perfluoropentane and iron oxide ( d 0 = 7.5 ± 0.35 nm) with a mean hydrodynamic diameter of 257.6 ± 10.9 nm are produced. siRNA (AllStars Hs cell death siRNA) is electrostatically bound to the particle surface and delivery to lung cancer cells and breast cancer cells is investigated with and without ultrasound exposure (500 kHz, 1 MPa peak‐to‐peak focal pressure, 40 cycles per burst, 1 kHz pulse repetition frequency, 10 s duration). The results show that siRNA functionality is not impaired by the treatment protocol and that the nanodroplets are able to successfully promote siRNA uptake, leading to significant apoptosis (52.4%) 72 h after ultrasound treatment. Abstract : Ultrasound responsive nanodroplets offer advantages over other delivery agents in terms of their ability to penetrate tumor tissue. Successful delivery of siRNA to both lung and breast cancer cell lines is demonstrated with no degradation of the therapeutic. In addition, magnetic targeting of the droplets and correlation between therapeutic effect and the energy of acoustic emissions are shown.